Financial Cryptography and Data Security 15th International Conference, FC 2011, Gros Islet, St. Lucia, February 28 - March 4, 2011, Revised Selected Papers - Danezis, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 15th International Conference on Financial Cryptography and Data Security, FC 2011, held in Gros Islet, St. Lucia, in February/March 2011. The 16 revised full papers and 10 revised short papers presented were carefully reviewed and selected from 65 initial submissions. The papers cover all aspects of securing transactions and systems and feature current research focusing on fundamental and applied real-world deployments on all aspects surrounding commerce security; as well as on systems security and inter-disciplinary efforts.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Data Encryption; Systems and Data Security; Management of Computing and Information Systems; Computers and Society; Computer Communication Networks; Algorithm Analysis and Problem Complexity